Protective Effect of Tat PTD-Hsp27 Fusion Protein on Tau Hyperphosphorylation Induced by Okadaic Acid in the Human Neuroblastoma Cell Line SH-SY5Y - Choi, Sunghyun (Cell Mol Neurobiol, 2015)
Alzheimer’s disease (AD) is an age-related disorder that causes a loss of brain function. Hyperphosphorylation of tau and the subsequent formation of intracellular neurofibrillary tangles (NFTs) are implicated in the pathogenesis of AD. Hyperphosphorylated tau accumulates into insoluble paired helical filaments that aggregate into NFTs; therefore, regulation of tau phosphorylation represents an important treatment approach for AD. Heat shock protein 27 (Hsp27) plays a specific role in human neurodegenerative diseases; however, few studies have examined its therapeutic effect. In this study, we induced tau hyperphosphorylation using okadaic acid, which is a protein phosphatase inhibitor, and generated a fusion protein of Hsp27 and the protein transduction domain of the HIV Tat protein (Tat-Hsp27) to enhance the delivery of Hsp27. We treated Tat-Hsp27 to SH-SY5Y neuroblastoma cells for 2 h; the transduction level was proportional to the Tat-hsp27 concentration. Additionally, Tat-Hsp27 reduced the level of hyperphosphorylated tau and protected cells from apoptotic cell death caused by abnormal tau aggregates. These results reveal that Hsp27 represents a valuable protein therapeutic for AD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10571-015-0199-1) contains supplementary material, which is available to authorized users.